Thematic and Functional-Style Diffuseness of Vocabulary in Modern Media Texts - Kostusiak, Nataliia; Shulska, Nataliia; Semashko, Tetiana; Tiutiuma, Tetiana; Masytska, Tetiana; Volianiuk, Inna; Sydorenko, Olha; Demeshko, Inna; Radko, Antonina; Sadivnycha, Maryna (My University, 2024)
The article characterizes the lexical units involved in the process of thematic diffusiveness, distinguishes between their regular and unique manifestations in modern journalism, outlines the secondary meaning of lexical-semantic derivatives and considers it in dichotomy with the interpretation established in dictionaries. Nominations with new semantic nuances, not yet recorded in dictionaries, contribute to the strengthening of expression and negative connotation. Such language units give texts an emotional and evaluative color, originality of language expression, non- standard implementation of the author’s communicative and intention. The stylistic migration of nominations is one of the important features of modern media discourse. Among them, the authors distinguish colloquial words, slangisms, in particular borrowed from the English language, vulgarisms, anti-etiquette idioms, which, although they are outside the limits of the standards typical for the press, give the statement a negative-reduced tone, aptly, emotionally and expressively characterize persons. Attention is focused on the writing of pejoratively labeled obscene vocabulary and the linguistic adaptation of anglicisms. It is noted that language units that have undergone interstylistic transitions occasionally have positive connotations. The analyzed factual material testified that in the all-Ukrainian media editions “Gazeta po-Ukrainsky” and “Ukraina moloda” nominations, which are characterized by stylistic migration, are quantitatively limited, which is explained by the internal politics of the publications.
Keywords: vocabulary; lexical meaning; semantic word structure; nomination; derivation; stylistic role; negative evaluation; slangism; invective vocabulary; Ukrainian language